Pengaruh LKPD pada Model Pembelajaran Kooperatif Tipe Pair Checks Terhadap Hasil Belajar Peserta Didik Kelas X SMA Negeri 1 Enrekang Kabupaten Enrekang (Studi Pada Materi Pokok Reaksi Reduksi-Oksidasi) - Diana Londong Salu; Army Auliah; Pince Salempa (ChemEdu, 2021)
This experiment was aimed to know the effect of using student wooksheet on the Cooperative Learning Pair Checks Type toward Student Learning Outcomes of Class X in Senior High School 1 Enrekang study on reduction-oksidation reaction. The independent variable in this reseach was student worksheet on the cooperative learning pair checks type, while the dependent variable was student’s learning outcomes. The Population in this reseach was all of student on class X SMAN 1 Enrekang with totaling 308 students which consist of 10 class. While the samples on this reseacrh where chosen by random, the class has been chosen was class X MIA 5 as a control with number of students are 34 people and class X MIA 7 as a experiment class with number of students are 26 people. Retrievel data of learning outcomes was achieved by using the pretest-posttest were analyzed using descriptive statistics and inferential statistics. The analysis descriptive statistics showed the average value of student learning outcomes experiment class and control class increased with average value of N-gain 0,609 and 0,509. Based on the analysis of inferentials statistic obtained tcount > ttable then H0 was rejected and H1 was accepted. It can be conclused that student worksheet on the Cooperative Learning Pair Checks Type have positive effect toward Student Learning Outcomes of Senior High School 1 Enrekang Class X on reduction-oksidation reaction topic.